Balancing Wilderness Protection and Economic Development: The Politics of Planning for Atikaki, 1972-1983 - Warecki, George (Ontario History)

(untitled) (The Ontario Historical Society, 2010)
This article is about the politics of planning for wilderness in northwestern Ontario. It blends environmental history and political science to discuss the relationships between diverse interests in provincial policy-making for the “Atikaki” region between Lake Winnipeg, Manitoba, and Red Lake, Ontario. In 1972, a Minnesota-based conservationist launched a campaign to establish a huge, interprovincial wilderness area encircled by a multiple-use buffer zone, to protect a canoeists’ paradise. Supporting conservation groups formed a coalition, opposed by local “productive” interests – forestry, mining, and fly-in fishing camp operators. The conflicted Ontario Ministry of Natural Resources reviewed the Atikaki proposal and weighed public input. When negotiations for a national park in Manitoba stalled in the late 1970s, the two provincial governments, recognizing key resource conflicts, replaced the original wilderness proposal with smaller, separate designs. Manitoba established Atikaki Provincial Park in 1985. Some 4,600 square kilometres on the Ontario side became Woodland Caribou Provincial Park in 1983.